2020
DOI: 10.1007/s41885-020-00066-z
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Cost of COVID Lockdowns: An Out-of-Equilibrium Analysis

Abstract: This paper estimates the cost of the lockdown of some sectors of the world economy in the wake of COVID-19. We develop a multi sector disequilibrium model with buyer-seller relations between agents located in different countries. The production network model allows us to study not only the direct cost of the lockdown but also indirect costs which emerge from the reductions in the availability of intermediate inputs. Agents determine the quantity of output and the proportions in which to combine inputs using pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 55 publications
2
127
0
3
Order By: Relevance
“…Our counterfactual simulations suggest that media coverage of COVID-19 in China may have averted 394,000 additional new infections from January 19 to February 29. Our results, along with earlier studies ( Chen et al, 2020b ; Gharehgozli et al, 2020 ; Kumar & Managi, 2020 ; Mandel & Veetil, 2020 ; Yoo & Managi, 2020 ), call for concerted efforts and actions to control and mitigate the impact of COVID-19.…”
Section: Discussionsupporting
confidence: 76%
“…Our counterfactual simulations suggest that media coverage of COVID-19 in China may have averted 394,000 additional new infections from January 19 to February 29. Our results, along with earlier studies ( Chen et al, 2020b ; Gharehgozli et al, 2020 ; Kumar & Managi, 2020 ; Mandel & Veetil, 2020 ; Yoo & Managi, 2020 ), call for concerted efforts and actions to control and mitigate the impact of COVID-19.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to studies analyzing the effect of non-legally binding policies such as those described above, others analyze the effect of an enforceable lockdown on the economy (Acemoglu et al 2020;Alvarez et al 2020;Farboodi et al 2020;Holtemöller 2020;Eichenbaum et al 2020;Gharehgozli et al 2020;Mandel and Veetil 2020;Martin et al 2020). Martin et al (2020) develop a microeconomic model to assess the socioeconomic effect of COVID-19 on individuals, estimating the direct effect of the lockdown policy on household income, consumption, and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Alvarez et al (2020) discuss the optimal lockdown policy to minimize the deaths and economic costs attributable to COVID-19, using the formulation as an optimization problem. Mandel and Veetil (2020) estimate the costs of a lockdown due to COVID-19 in some sectors of the global economy using a multi-sector disequilibrium model that considers the buyer-seller relationship between agents in different countries. However, none consider stigma in their scope of research.…”
Section: Introductionmentioning
confidence: 99%
“…The United States has witnessed one of the worst outbreaks of the COVID-19 pandemic. Widespread cases, high rates of mortality, lockdown of services, the shutdown of businesses, and nationwide layoffs have led to a severe social and economic disruption of routine American life [1,2]. As a result, in an April 2020 Kaiser Family Foundation (KFF) poll, 72% of American adults reported that their lives had been disrupted "a lot" or "somewhat" by the Coronavirus outbreak.…”
Section: Introductionmentioning
confidence: 99%